2021
DOI: 10.3390/ma14144048
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of Thin ZnO Films Deposited by ALD under O-Rich and Zn-Rich Growth Conditions and Their Relationship with Electrical Parameters

Abstract: The structural, optical, and electrical properties of ZnO are intimately intertwined. In the present work, the structural and transport properties of 100 nm thick polycrystalline ZnO films obtained by atomic layer deposition (ALD) at a growth temperature (Tg) of 100–300 °C were investigated. The electrical properties of the films showed a dependence on the substrate (a-Al2O3 or Si (100)) and a high sensitivity to Tg, related to the deviation of the film stoichiometry as demonstrated by the RT-Hall effect. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 65 publications
(134 reference statements)
1
10
0
Order By: Relevance
“…While this study suggested a low-temperature crystalline-free amorphous film is preferable for achieving a long lifetime, the unreacted precursor ligands and byproducts were another inevitable issues associated with the low-temperature ALD processes. These impurities could substantially change the film properties, such as electronic and ionic transport properties, mechanical stability, and chemical reactivity 21 24 , which may open another pathway to breaking the current protection lifetime limit. In this paper, we report a fundamental discovery of the detrimental role of the residual Cl ligand in amorphous TiO 2 films to the PEC protection lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…While this study suggested a low-temperature crystalline-free amorphous film is preferable for achieving a long lifetime, the unreacted precursor ligands and byproducts were another inevitable issues associated with the low-temperature ALD processes. These impurities could substantially change the film properties, such as electronic and ionic transport properties, mechanical stability, and chemical reactivity 21 24 , which may open another pathway to breaking the current protection lifetime limit. In this paper, we report a fundamental discovery of the detrimental role of the residual Cl ligand in amorphous TiO 2 films to the PEC protection lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…We have used integral width in the Debye–Scherrer model [ 20 ] instead of FWHM of diffraction peaks to get more accurate crystallite size. Analysis of XRD data using the Debye–Scherrer model reveals average crystallite size increases from ≈100 to 200 nm for ZnO/HR‐Si after successive RTP treatment temperature from 400 °C to 800 °C ( Figure ), which is in accordance with results reported for undoped ZnO films.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of XRD data using the Debye–Scherrer model reveals average crystallite size increases from ≈100 to 200 nm for ZnO/HR‐Si after successive RTP treatment temperature from 400 °C to 800 °C ( Figure ), which is in accordance with results reported for undoped ZnO films. [ 20 ] This may be explained by accounting coalescence for small crystallite domains thermally produced by diffusion at their boundaries, resulting in increased crystallite growth. [ 21 ] The transfer of atoms at grain boundaries from one crystallite to another is the process of crystallite development, and the ultimate crystallite size is determined by the annealing conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5(c). The lattice mismatch strain is relaxed by generating dislocations that are strongly correlated with the electrical conductance behavior (Moon et al, 2012;Mishra et al, 2021). It is noteworthy that the as-grown ZnO thin film is in a compressive state compared with the bulk c-lattice constant of 5.213 A ˚.…”
Section: Conceptual Design Of Multimodal X-ray Probe Stationmentioning
confidence: 99%